Escritura y danza, una lectura psicoanalítica de las creaciones artísticas en la infancia - Herrera González, Damián (2023)
Participantes: Andreina Araya Villalobos Amanda Sofía Pérez Ramírez Astrid Ruiz Carranza Ciara Victoria Alvarado Chávez Dana Peña Rodríguez Fabiana Gómez Cuadra Isabella Hernández Campos Jessica Mata Ramírez Mathias Herrera Castro Nayeli Barrantes Carranza Samira López Rojas Tamara Delgado Duarte Violeta López Cabrero